2015
DOI: 10.1371/journal.pone.0129033
|View full text |Cite
|
Sign up to set email alerts
|

Differential Analysis of the Secretome of WRL68 Cells Infected with the Chikungunya Virus

Abstract: The Chikungunya virus (CHIKV) is an arthropod borne virus. In the last 50 years, it has been the cause of numerous outbreaks in tropical and temperate regions, worldwide. There is limited understanding regarding the underlying molecular mechanisms involved in CHIKV replication and how the virus interacts with its host. In the present study, comparative proteomics was used to identify secreted host proteins that changed in abundance in response to early CHIKV infection. Two-dimensional gel electrophoresis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
(43 reference statements)
0
10
0
Order By: Relevance
“… 79 Secretomes analysis also identifies the proteins in CM, which can be used as biomarker identification for specific diseases and in drug identification and development. 80 Therefore, studies on secretomes provide insight into tissue engineering and regenerative medicine.…”
Section: Secretomesmentioning
confidence: 99%
“… 79 Secretomes analysis also identifies the proteins in CM, which can be used as biomarker identification for specific diseases and in drug identification and development. 80 Therefore, studies on secretomes provide insight into tissue engineering and regenerative medicine.…”
Section: Secretomesmentioning
confidence: 99%
“…Early evidence indicated that in different human pathologies the cellular dysfunction of different cell types including dermal fibroblasts leads to an aberrant secretome that reprograms the microenvironment and induces myofibroblast differentiation [15,16]. Hence, in pathologic conditions the secretome changes may serve to disclose disease-specific biomarkers with a possible therapeutic relevance [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…The non-correlation between transcription levels and amounts of secreted protein indicates that secretion is regulated by some not-yet disclosed mechanism, involving transcription, translation, storage, sorting, and transport, as already reported for other systems [ 91 ]. This non-correlation was also observed when the exoproteome of WRL-68 human hepatic cells infected with the chikungunya virus was analyzed [ 92 ].…”
Section: Resultsmentioning
confidence: 73%